Reclassification and treatment of odontogenic keratocysts: A cohort study - Ophir Ribeiro-Júnior; Alexandre Meireles Borba; Carlos Augusto Ferreira Alves; Marcia Maria de Gouveia; Maria Cristina Zindel Deboni; Maria da Graça Naclério-Homem (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: The odontogenic keratocyst (OKC) is a recurrent cyst that has been recently reclassified from an odontogenic tumor to an odontogenic cyst. The aim of the present study was to investigate its treatment and address issues related to its association with nevoid basal cell carcinoma syndrome (NBCCS). Lesions from the cohort of patients included in the present study consisted of 40 OKCs, of which 27 lesions were treated by enucleation (GE) and 13 underwent decompression (GD). Complementary treatment occurred in 38 (95%) lesions, of which 10 underwent isolated peripheral ostectomy (GO) and 28 underwent peripheral ostectomy combined with Carnoy's solution (GC). Thirteen lesions were associated with NBCCS (GS), while the others (n=27) were non-syndromic lesions (GnS). The recurrence-free periods (RFP) in the sample groups were compared using the Kaplan-Meier function and log-rank test at a significance level of 5% (p < 0.05) and were used to calculate the cumulative risk of recurrence (CRR) in each postoperative year. During the follow-up period, which had a mean of 43.5 months (range: 12-102 months), six (15%) recurrences were diagnosed. There was no significant difference among the RFP for the compared groups (p > 0.05) or increased CRR for the decompression (15.4%) over five years. Application of Carnoy's solution did not increase the efficacy of the peripheral ostectomy, but was related to a CRR of 0% for the syndromic lesions over five years. Therefore, 1) decompression did not increase the recurrence risk; 2) peripheral ostectomy demonstrated a similar efficacy as the combination with Carnoy's solution; 3) the association of NBCCS did not seem to significantly influence OKC recurrence; and 4) syndromic lesions seem to behave in the same manner as non-syndromic lesions when submitted to complementary treatments.